The Defining Characteristics of Human Language: A Comprehensive Analysis - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 10 No 2 (2025): Journal of Advanced Research in English and Education, 2025)
This article delves into the intricate characteristics and fundamental features that define human language. Language, a cornerstone of human cognition and social interaction, is a complex system that transcends mere communication. This work aims to systematically unpack ten core attributes, including its symbolic nature, displacement, duality of patterning, productivity, arbitrariness, cultural transmission, and its structural hierarchical organization. We explore how these features collectively enable the sophisticated and infinite expressiveness of human thought. The abstract further addresses the distinction between human language and animal communication systems, highlighting how the unique confluence of these characteristics underpins our ability to discuss abstract concepts, create new meanings, and transmit knowledge across generations. By synthesizing scholarly perspectives, the article provides a comprehensive overview that is essential for students and researchers in linguistics, psychology, and cognitive science. The discussion underscores that language is not merely a tool but a defining aspect of what it means to be human, shaping our perception of reality and our social structures. This exploration provides a foundational understanding of language, which is crucial for appreciating its role in culture, education, and human development.